Validation of the Malay Version of Hospital Anxiety and Depression Scale (HADS) in Hospital Universiti Sains Malaysia - Yahya, Fariza; Othman, Zahiruddin (Japan International Cultural Exchange Foundation, 2015)
Objective: To validate the translated Malay version of the HADS and determine the optimal cutoff point and respective sensitivity and specificity. Design: Cross sectional study. Muteriuls and Methods: Sixty cases and 60 controls were assessed using the Malay version of HADS followed by interviewed using Hamilton Rating Scale for Anxiety (HDRS), Hamilton Rating Scale for Depression (HARS) and then reassessed by using the fourth edition of Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) to establish the diagnosis. Results: The best cutoff point was 8/9. Sensitivity 90.07o and specificity 86.2oh for anxiety and sensitivity 93.2"h and specificity 90.8"/o for depression was detected Conclusion: Malay version of HADS showed a good sensitivity and specificity and therefore is valid instrument for use in a Malaysia population.